2021
DOI: 10.1016/j.bbrc.2021.09.024
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 triggers DNA damage response in Vero E6 cells

Abstract: The novel severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) virus responsible for the current COVID-19 pandemic and has now infected more than 200 million people with more than 4 million deaths globally. Recent data suggest that symptoms and general malaise may continue long after the infection has ended in recovered patients, suggesting that SARS-CoV-2 infection has profound consequences in the host cells. Here we report that SARS-CoV-2 infection can trigger a DNA damage response (DDR) in African g… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 27 publications
(30 reference statements)
0
32
0
Order By: Relevance
“… 50 In accordance with DNA repair, the DNA damage response was triggered by SARS-CoV-2 in Vero E6 cells. 51 …”
Section: Resultsmentioning
confidence: 99%
“… 50 In accordance with DNA repair, the DNA damage response was triggered by SARS-CoV-2 in Vero E6 cells. 51 …”
Section: Resultsmentioning
confidence: 99%
“…Thus, an energy shift occurs resulting in increased ROS production, oxidative stress and DNA damage/DNA Damage Response (DDR) pathway activation. In addition, DDR and the subsequent cell cycle arrest may be driven by an interaction of Coronavirus nsp13 protein and DNA polymerase δ [ 54 ] and SASP via the cGAS/STING and other DNA damage dependent pathways ( Figure S8 ). Therefore, our previous work showing that DNA damage/DDR is a potent inducer of senescence, signifies its importance in the establishment of the viral induced senescence phenotype [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Concordantly, the ATR inhibitor berzosertib completely inhibits the replication of SARS-CoV, MERS-CoV and SARS-CoV-2 in epithelial cell lines, demonstrating that the replication of the novel coronavirus depends on ATR-dependent DNA-repair mechanisms [ 47 ]. Another recent study found that SARS-CoV-2 infection induces overexpression of ATR and CHK1 in viral host Vero E6 cells [ 48 ]. This effect was accompanied with increased phosphorylation levels of ATR, CHK1 and H2AX [ 48 ].…”
Section: Potential Direct Mechanisms Of Coronaviruses To Induced Dna Damagementioning
confidence: 99%
“…Another recent study found that SARS-CoV-2 infection induces overexpression of ATR and CHK1 in viral host Vero E6 cells [ 48 ]. This effect was accompanied with increased phosphorylation levels of ATR, CHK1 and H2AX [ 48 ]. At the genomic level, SARS-CoV-2 infection resulted in telomere shortening, which is a documented marker of cell senescence [ 48 ].…”
Section: Potential Direct Mechanisms Of Coronaviruses To Induced Dna Damagementioning
confidence: 99%
See 1 more Smart Citation